The hut as place for "interior immensity". The sense of dwelling in Henry David Thoreau - Di Chiro, Antonio (Itinerari, 2024)
The path articulated in this paper has as its horizon the question of dwelling. This question will be analyzed in relation to a particular type of dwelling that is the hut. In this regard, we will focus on the hut built by Henry David Thoreau on the shores of Walden Lake in 1854 as a protected and privileged place of intimacy and a place that allows for reflection on oneself and one’s being in the world.